LPV design of fault-tolerant control for road vehicles - Gáspár, Péter; Szabó, Zoltán; Bokor, József (Zielona Góra: Uniwersytet Zielonogórski)
The aim of the paper is to present a supervisory decentralized architecture for the design and development of reconfigurable and fault-tolerant control systems in road vehicles. The performance specifications are guaranteed by local controllers, while the coordination of these components is provided by a supervisor
Keywords: robust control; fault detection; LPV systems; fault-tolerant control; vehicle dynamics; vehicle control